2022
DOI: 10.34172/jhp.2022.49
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic activity of Astragalus brachycalyx subsp. brachycalyx extract against hydatid cyst protoscoleces and its effect on induction of apoptosis: an in vitro and ex vivo study

Abstract: Introduction: This study aims to evaluate in vitro and ex vivo antiparasitic activity of Astragalus brachycalyx subsp. brachycalyx. root chloroformic extract against hydatid cyst protoscoleces and its effect on induction of apoptosis. Methods: Various concentrations of the A. brachycalyx root chloroformic extract (56.25, 112.5, 225, and 450 mg/mL) were treated with hydatid cyst protoscoleces collected from the liver of infected sheep for 5-60 minutes in vitro and ex vivo. Eosin exclusion test was also utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Regarding the antimicrobial mechanisms of flavonoids and phenolic compounds, previous studies confirmed that these compounds displayed their antimicrobial mechanisms through the suppression of nucleic acid synthesis, blockage of cytoplasmic membrane function, suppression of energy metabolism, prevent bacterial virulence factors, display of a synergistic effect with current synthetic drugs, etc. [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the antimicrobial mechanisms of flavonoids and phenolic compounds, previous studies confirmed that these compounds displayed their antimicrobial mechanisms through the suppression of nucleic acid synthesis, blockage of cytoplasmic membrane function, suppression of energy metabolism, prevent bacterial virulence factors, display of a synergistic effect with current synthetic drugs, etc. [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The specimens were then examined through direct and formalin-ether methods (9). In the next step, the sucrose 0.85 M gradient technique was used to concentrate Giardia cysts (10). The specimens were then diluted with distilled water (12:1) and shaken for 5 minutes to obtain an aqueous solution.…”
Section: Methodsmentioning
confidence: 99%
“…The activity of caspase-3 in protoscoleces after incubation with FMN was studied based on a commercial colorimetric protease kit (Sigma, Germany) according to the producer protocols (20).…”
Section: Effect Of Caspase-3 Activity In Protoscolecesmentioning
confidence: 99%